The Micropaleontology Collection at the Laboratory of Historical Geology and BioGeosciences (National and Kapodistrian University of Athens, Greece) - Maria Triantaphyllou; Vasiliki-Grigoria Dimou; Elisavet Skampa; Katerina Kouli; Theodora Tsourou; George Kontakiotis; Evangelia Besiou; Margarita Dimiza; Elizabeth Stathopoulou; Hara Drinia; Assimina Antonarakou (Revue de Micropaléontologie, 2026)

Towards an Integrated and Accurate Planktonic-Foraminiferal-Deduced Bio-Chrono-Stratigraphic Framework of Late Quaternary Mediterranean Marine Cores - George Kontakiotis; Assimina Antonarakou; Evangelia Besiou; Elisavet Skampa; Maria V. Triantaphyllou (Journal of Marine Science and Engineering, 2023)
The late Quaternary is a key stratigraphic interval as it encompasses the Late Glacial to Holocene transition, which is characterized by a series of pronounced centennial climate oscillations and subsequent short-term events of paleoceanographic variability. Across this stratigraphic interval, significant turnovers and faunal changes in the composition and abundance of planktonic foraminiferal assemblages are well-documented through their high-resolution quantitative analysis performed in the south Aegean core NS-18. The identification of 10 synchronous bioevents among the Mediterranean sub-basins allows accurate inter-basinal correlations over the study time interval, thus contributing to the development of a robust chronostratigraphic framework for this setting. Moreover, the identification and timing of additional 20 diachronous bioevents, in conjunction with the already established bio-ecozonation scheme of the Aegean Sea, provide a continuous record of faunal changes (in terms of species-specific distributional abundances) which can be used as an additional locally expressed biochronological tool for the eastern Mediterranean deep-sea cores. The present study certainly indicates that the cause-and-effect relationships between the paleoceanographic/paleoclimatic perturbations and biological response require a highly resolved regional chronostratigraphy.

Closed‐Loop Supply Chains for Photovoltaic Panels: A Case‐Based Approach - Maria Besiou; Luk N. Van Wassenhove (Journal of Industrial Ecology, 2016)
Summary Photovoltaic (PV) waste is expected to significantly increase. However, legislation on producer responsibility for the collection and recovery of PV panels is limited to the European Union (EU) Waste Electrical and Electronic Equipment Directive Recast, which lays down design, collection, and recovery measures. Academic knowledge of closed‐loop supply chains (CLSCs) for PV panels is scarce. We analyze the supply chain using multiple cases involving the main stakeholders in the design, production, collection, and recovery of PV panels. Our article answers two research questions: How does the PV supply chain operate, and what are critical factors affecting the reverse supply chain management of used panels? Our research seeks to fill the gap in the CLSC literature on PV panels, as well as to identify barriers and enablers for PV panel design, collection, and recycling.

Feasibility of Using Radio Frequency Identification to Facilitate Individual Producer Responsibility for Waste Electrical and Electronic Equipment - Maurice O'Connell; Stewart Hickey; Maria Besiou; Colin Fitzpatrick; Luk N. Van Wassenhove (Journal of Industrial Ecology, 2013)
Summary Regulatory measures that hold producers accountable for their products at end of life are increasingly common. Some of these measures aim at generating incentives for producers to design products that will be easier and cheaper to recover at the postconsumer stage. However, the allocation of recovery costs to individual producers, which can facilitate realization of the goals of these policies, is hindered by the practical barrier of identification and/or sorting of the products in the waste stream. Technologies such as radio frequency identification (RFID) can be used for brand or model recognition in order to overcome this obstacle. This article assesses the read rate of RFID technology (i.e., the number of successful retrievals of RFID tag data [“reads”] in a given sample of tagged products) and the potential role of RFID tags in the management of waste electrical and electronic equipment (WEEE) at current levels of technical development. We present the results of RFID trials conducted at a civic amenity site in the city of Limerick, Ireland. The experiment was performed for fixed distances up to 2 meters on different material substrates. In the case of white goods (i.e., large household appliances), a 100% read rate was achieved using an RFID handheld reader. High read rates were also achieved for mixed WEEE. For a handheld scan of a steel cage containing mixed WEEE, read rates varied from 50% to 73% depending on the ultrahigh frequency (UHF) metal mount tag employed and the relative positioning of the tags within the cage. These results confirm that from a technical standpoint, RFID can achieve much greater brand or model identification than has been considered feasible up to now, and thus has a role to play in creating a system that allocates recovery costs to individual producers.